Analisis Ditribusi Spasial Kasus Tuberkulosis Di Wilayah Denpasar Timur Dengan Pendekatan Sistem Informasi Geografis - Budiartana, Wayan; Mulana, Viktorinus Alfred Saptiono; Farmani, Putu Ika (Jurnal Epidemiologi Kesehatan Komunitas, 2025)
Background: The East Denpasar area has shown an increasing trend in TB cases from 2021 to 2023, with a significant rise noted in 2023. This study aims to analyse the spatial distribution of TB cases in East Denpasar using a Geographic Information System (GIS).Methods: The descriptive quantitative with a GIS approach conducted using 68 patients, focusing on socio demographic variables, TB classification, treatment outcomes, and treatment history. TB case data in East Denpasar for 2023 was collected from two PHC of East Denpasar and analysed by ArcMap. The analysis includes colour gradient maps, dot maps, and graphic maps. The study identifies, and maps high-cluster locations of TB cases based on treatment history and outcomes.Result: The characteristic responden are private employees (42,65%), 26-45 y.o (47,06%), and female (52.94%). The colour gradient map analysis shows that Kesiman Kertalangu has the highest distribution. Based on the dot map, a high concentration is seen in Kesiman Kertalangu and Penatih. The graphic map analysis shows a comparison of TB treatment history, where most patients are new patients, and a comparison of treatment outcomes shows that most patients have recovered.Conclusion: This study concludes that the productive age group (26-45 years) and private employees are the most vulnerable population to TB. Kesiman Kertalangu has the highest number of TB cases, with a higher distribution of pulmonary TB compared to extrapulmonary TB. This area also has the highest number of new patients and patients who have not completed treatment.